Evaluasi Penerapan Pengendalian Internal Divisi Pemberdayaan Ekonomi Lembaga Badan Amil Zakat Nasional Menggunakan ErmCoso Framework - Rahmat, Paisal; Lubis, Fadhila Hanum (Studia Economica : Jurnal Ekonomi Islam, 2024)
This study aims to determine the application of internal control in the economic empowerment division at the zakat management institution using the ERM-COSO Framework. Good internal control implementation is needed to achieve good performance in an organization. The object of this research is the National Amil Zakat Agency. The research method used is descriptive qualitative method using interview instruments. The interviewees in this research are the top management division and the person in charge at the zakat management institution which is the object of research. The results of this study indicate that the National Amil Zakat Agency has implemented internal control using the ERM-COSO Framework by 68%, which means that the implementation of internal control is quite effective..